The impact of digital start-up founders’ higher education on reaching equity investment milestones - Ratzinger, Daniel; Amess, Kevin; Greenman, Andrew; Mosey, Simon (Springer, 2018)
This paper builds on human capital theory to assess the importance of formal education among graduate entrepreneurs. Using a sample of 4.953 digital start-ups the paper evaluates the impact of start-up founding teams’ higher education on the probability of securing equity investment and subsequent exit for investors. The main findings are: (1), teams with a founder that has a technical education are less likely to remain self-financed and are more likely to secure equity investment and to exit, but the impact of technical education declines with higher level degrees, (2) teams with a founder that has doctoral level business education are less likely to remain self-financed and have a higher probability of securing equity investment, while undergraduate and postgraduate business education have no significant effect, and (3) teams with a founder that has an undergraduate general education (arts and humanities) are less likely to remain self-financed and are more likely to secure equity investment and exit while postgraduate and doctoral general education have no significant effect on securing equity investment and exit. The findings enhance our understanding of factors that influence digital start-ups achieving equity milestones by showing the heterogeneous influence of different types of higher education, and therefore human capital, on new ventures achieving equity milestones. The results suggest that researchers and policy-makers should extend their consideration of universities entrepreneurial activity to include the development of human capital.